The development of physic learning device by using problem based learning model approach characters value integration to increase learning out put - Eko Ambar Wibowo; Festiyed Festiyed; Djusmaini Djamas (International Conferences on Educational, Social Sciences and Technology)
The standard of content and the standard of process of curriculum 2013 require scientific learning and scientific learning character with more active studentsespecially in learning physics. Development model that was applied in this research was 4-D, which consists of defining, designing, developing and disseminating stages. Defining stagecovered curriculum, material and the student analysis. Designing stage covered the activity of formulating learning device in form of syllabus, Learning Implementation Plan, Module, Student Worksheet, the assessment of knowledge competition, manner, characters, and skills. On development stage the test of validity were done through validity sheet of learning device, practicality testing through observation sheet on the using lesson plan, questionnaire response of the teachers and the students, affectivity testing were obtained from the assessment of knowledge, attitude, characters, skill, and questionnaire of student’s response. Disseminating stage is the activity to disseminate learning device valid, practice, and effective